Tumor Hypoxia Drives Genomic Instability - Tang, Ming; Bolderson, Emma; O’Byrne, Kenneth J.; Richard, Derek J. (Frontiers in Cell and Developmental Biology, 2021)
Cancer is a leading cause of death worldwide. As a common characteristic of cancer, hypoxia is associated with poor prognosis due to enhanced tumor malignancy and therapeutic resistance. The enhanced tumor aggressiveness stems at least partially from hypoxia-induced genomic instability. Therefore, a clear understanding of how tumor hypoxia induces genomic instability is crucial for the improvement of cancer therapeutics. This review summarizes recent developments highlighting the association of tumor hypoxia with genomic instability and the mechanisms by which tumor hypoxia drives genomic instability, followed by how hypoxic tumors can be specifically targeted to maximize efficacy.